2017
DOI: 10.1039/c6ib00240d
|View full text |Cite
|
Sign up to set email alerts
|

Protein self-assembly following in situ expression in artificial and mammalian cells

Abstract: The self-assembly of proteins has been widely studied in controlled in vitro conditions, and more recently in biological environments. The self-assembly of proteins in biology can be a feature of the pathogenesis of protein condensation disease, or can occur during normal physiological function, for example during the formation of intracellular non-membrane bound organelles. To determine the mechanisms for the assembly process fully, controlled in vitro experiments using purified protein solutions are often re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has been reported that proteins with somatic mutations often cause intracellular aggregation that can occur in a diseased state or during normal physiological functions. This mechanism is clearly related to the folding ability of proteins because the wild type counterpart no longer shows aggregation (31,34). Taken together these mechanisms on misfolded protein aggregates in mammalian cells, recombinant CTAs aggregated particles observed in the cells are categorized to the compartment of insoluble protein deposit (IPOD) (32,33).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that proteins with somatic mutations often cause intracellular aggregation that can occur in a diseased state or during normal physiological functions. This mechanism is clearly related to the folding ability of proteins because the wild type counterpart no longer shows aggregation (31,34). Taken together these mechanisms on misfolded protein aggregates in mammalian cells, recombinant CTAs aggregated particles observed in the cells are categorized to the compartment of insoluble protein deposit (IPOD) (32,33).…”
Section: Discussionmentioning
confidence: 97%
“…In mammalian cells, misfolded proteins are considered to be toxic (28)(29)(30). Therefore, mammalian cells possess degradation pathways for the removal of misfolded proteins, including the ubiquitin-proteasome system, chaperone-mediated autophagy, and macroautophagy (31).…”
Section: Discussionmentioning
confidence: 99%